Kesiapan Sosial dalam Adopsi Teknologi Gravity-driven Membrane (GDM) di Wilayah 3T Indonesia - Irawan, Mia Monica Ayu Putri (Jurnal Sosiologi Andalas, 2025)
This study addresses the persistent challenge of limited access to clean water in Indonesia’s outermost, remote, and underdeveloped (3T) regions, where communities rely on vulnerable sources such as rainwater, rivers, and shallow wells. While gravity-driven membrane (GDM) technology offers a low-cost, chemical- and electricity-free solution, its adoption remains limited despite proven technical effectiveness. This research explores how social readiness and structural conditions shape GDM adoption, focusing on community perceptions, cultural meanings of rainwater, and inequalities in state-led water development. Using a qualitative narrative literature review of studies published between 2015 and 2025, the analysis applies sociological frameworks of the Social Construction of Technology (SCOT), ecological justice, and social-ecological resilience. Findings reveal that: (1) GDM reliably removes turbidity, bacteria, and organic matter without external inputs; (2) local perceptions and cultural framings significantly influence acceptance; and (3) top-down water governance perpetuates structural exclusion. The study contributes to sociological scholarship by extending SCOT’s application to community-based water technologies in marginalized regions, highlighting that successful GDM implementation requires participatory, bottom-up approaches integrating technical innovation with ecological justice and social resilience.